High immunity and low mortality after Omicron and mass event in Cameroon despite low vaccination - Yap Boum II; Lucrece Matchim; Dominique K. Guimsop; Bongkiyung D. Buri; Lisa M. Bebell; Yuya S.F. Jaudel; Fai K.G. Njuwa; Daniel B. Danirla; Eric Youm; Rodrigue Ntone; Claudric Roosevelt Tchame; Dora Tchiasso; et al. (Journal of Public Health in Africa)
Background: Little is known about the evolution of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) immunity in African communities.